Cuba in global politics – geopolitics through cross-impact analysis / Cuba en la política global – Geopolítica a través del análisis de impacto cruzado - Auffermann Burkhard; Kaivo-oja Jari; Luukkanen Jyrki; Laitinen Jasmin (Cuba, 2025)
This paper focuses on Cuba and its position in global politics by means of geopolitics/geoeconomics. These two concepts are used to describe the current international political dimensions and how different nations attempt to control their position within global power politics. Geopolitics has always been related to the energy economy and energy policy. Cuba has throughout history been heavily connected to the states located in its neighbourhood as well as the international power politics. In this article, we illustrate the impacts of geopolitics and further explain the Cuban dependency on international global politics through Cross-Impact analysis (CIA), especially in terms of its version called Express Cross-Impact Technique (EXIT), developed at Finland Futures Research Institute. Three alternative scenarios are the results of the analysis.
Programa General y Técnico: CONVENCIÓN CIENTÍFICA DE INGENIERÍA Y ARQUITECTURA DE LA CUJAE, 20 CCIA 2022